The improvement on vibration isolation performance of hydraulic excavators based on the optimization of powertrain mounting system - Mian Jiang; Shoushi Liao; Yong Guo; Jigang Wu (Advances in Mechanical Engineering, 2019)
In this article, the improvements on vibration isolation performance of hydraulic excavators are achieved via the optimization of powertrain mounting system. The powertrain is viewed as a rigid body and described by a 6-degree-of-freedom model. The rigid-flexible coupling model of hydraulic excavators is carried out based on software ADAMS, in which the influences from the mass and elastic deformation of base are considered. In the process of optimization for the powertrain mounting system, energy decoupling rate and vibration transmissibility are set to be the objective functions, while the stiffness coefficients in three directions of the mounting coordinate systems are chosen as the designed variables. With the given constrained conditions of these variables, nondominated sorting genetic algorithm II is employed to optimize the stiffness coefficients of suspension elements. The simulations for the rigid-flexible coupling model with the optimized mounting system show that the vibration isolation performances of hydraulic excavators are improved comparing with that with non-optimized powertrain mounting system.